Pain at chronic pancreatitis: origin and treatment options - V. T. Ivashkin; K. V. Ivashkin; A. V. Okhlobystin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present basic mechanisms of pain at pancreatitis and determine main management approaches in pain-predominant cases.Summary. Direct toxic action of damaging factors (first of all — alcohol), pancreatic enzyme deviation phenomenon, parenchymal damage by overflow of free radicals, elevation of intraductal pressure, damage of nerves (neuropathic pain) and compression of adjacent organs play primary role in development of pain. Enzyme supplements at chronic pancreatitis can be indicated not only as replacement treatment, but also as addition to complex treatment of patients with severe abdominal pain. Proton pump inhibitors, spasmolytics or prokinetics are recommended as additional therapy. At absence of desirable results application of nonsteroid anti-inflammatory drugs and analgetics, in resistant pain — non-narcotic opiates or pregabalin are indicated. Efficacy of analgetics can be increased by coadministration of psychotropic agents, most often — tricyclic antidepressants. In severe cases intractable pain at a chronic pancreatitis itself can become indication to surgical intervention.Conclusion. Treatment efficacy in each given case depends on duly establishment and adequate treatment of complications, motivation for abstain of alcohol intake and smoking; strict diet restriction for relapse period, and functional rest for the pancreas.